Development and testing of hybrid timber-steel braced frames. (1st November 2019) - Gilbert, Colin F.; Erochko, Jeffrey
Highlights: Glued-in rod fasteners were used to adapt advanced structural bracing systems into heavy timber buildings. A capacity-design procedure was developed for seismic applications of braced timber frames. The hybrid timber-steel braced frame exhibited excellent wind and seismic performance. The testing provided validation of glued-in rod fasteners for capacity protected braced frame connections. European glued-in rod design procedures were evaluated for applications in North America. Abstract: The practical use of high-performance structural steel bracing systems in heavy timber buildings has not previously been explored. This study investigates the design and behavior of a prototype steel beam to column bracing connection to enable the use of friction damping devices, buckling restrained braces (BRBs) and other high-performance braces to create hybrid timber-steel braced frames. Glued-in rods, with and without pre-tensioning, are used to connect the steel and timber elements in the frame. The timber elements and connections are designed to remain elastic using capacity design principles, allowing the frame to behave similarly to comparable steel high-performance braced frames. A test frame incorporating the new hybrid beam to column bracing connection system with a friction brace device was evaluated and validated using a half scale test of a beam-column-brace connection under wind loading and BRB qualification protocol loading. The tests showed that the connections and timber members remained elastic and could accommodate at least two times the design drift at full load. They also showed that pre-tensioning the glued-in rod connections did not affect the global system performance.